Sentidos e perspectivas atribuídos por crianças à sua condição de estar para adoção - Ferreira, Emmanuelle de Oliveira (2010)
Considering the Brazilian current context, where many children are in institutional shelter waiting for adoption, the aim of this study was to know the meaning that sheltered children (whose families had already lost their custody or were in the process of losing it, at the moment of the field work) gave to their adoption condition. The research was carried out with three children in the shelter where they lived, in Natal, Rio Grande do Norte, Brazil. The field work took six months approximately. In order to meet the objective of this research, individual procedures were structuralized using figures and drawing material. With these procedures the children could speak directly or indirectly about the application of the legal measure of institutional shelter, about their lives before the application of this legal measure and what happened since then, and their original families and future perspectives. The content of the procedures was tape recorded and registered in the field work diary. The analysis of the corpus occurred with the Thematic Content Analysis, considering the theoretical methodological perspective of the Net of Meanings approach. The analysis of the corpus showed the ambiguity of the children, who consider good to live in the institution where they are, recognizing the responsibility of the original caregivers for their sheltered condition and, at the same time, they miss their relatives and wish to be with them. The subjects recognize the perspective of adoption and imagine it in a positive way. However, when the children were questioned about what could happen to them in the future, they said that they did not know, expressing uncertainty concerning their destinations